2017
DOI: 10.1007/s00701-017-3118-z
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial pressure monitoring after primary decompressive craniectomy in traumatic brain injury: a clinical study

Abstract: Intracranial hypertension and/or low CPP occurs frequently after primary DC; their occurence is associated with an unfavorable neurological outcome. ICP monitoring appears useful in guiding therapy after primary DC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 33 publications
2
23
0
1
Order By: Relevance
“…Leitgeb et al described a large series of patients who had surgery as a primary procedure for sTBI with an early mortality rate of 46.7% and only 32.2% of the patients experienced a favorable outcome. Moreover, the results in terms of ICP control in our cohort were remarkable, noting that primary DC has been associated with a persistent intracranial hypertension in a high percentage of patients, as described by the group of Servadei [29]. In their study, despite primary DC, a further interventional treatment was necessary in a high rate of patients (barbiturate coma 20.6%, external ventricular drainage 11.8%, and DC diameter widening 2.9%).…”
Section: Discussionsupporting
confidence: 56%
“…Leitgeb et al described a large series of patients who had surgery as a primary procedure for sTBI with an early mortality rate of 46.7% and only 32.2% of the patients experienced a favorable outcome. Moreover, the results in terms of ICP control in our cohort were remarkable, noting that primary DC has been associated with a persistent intracranial hypertension in a high percentage of patients, as described by the group of Servadei [29]. In their study, despite primary DC, a further interventional treatment was necessary in a high rate of patients (barbiturate coma 20.6%, external ventricular drainage 11.8%, and DC diameter widening 2.9%).…”
Section: Discussionsupporting
confidence: 56%
“…They reported that neurological outcomes did not differ between the patient groups with ICP monitoring and without ICP monitoring. On the contrary, in a retrospective study by Picetti et al, [25] authors evaluated the clinical follow-up in 34 patients after primary DC following emergency hematoma evacuation. They noted that the knowledge of ICP values might be helpful in guiding therapy after primary DC.…”
Section: Discussionmentioning
confidence: 99%
“…As many as three consensus conferences have tried to address this and other controversies and uncertainties [2,3,8]. One of the recommendations was that BICP monitoring is generally recommended following a secondary decompressive craniectomy (DC) in order to assess the effectiveness of DC, in terms of ICP control, and guide further therapy^ [8].Indeed there exists plentiful information from recent trials (DECRA and RESCUEicp) about situations where DC was employed to control rising ICP refractory to maximal medical therapy [4,6]; this being secondary DC.One of the gaps in our knowledge, and the main objective of the featured study by Picetti et al [7], was to explore the role of ICP monitoring in traumatic brain injury (TBI) patients after primary decompressive craniectomy. BPrimary^in this context refers to DC during evacuation of an intracranial lesion in the acute phase.…”
mentioning
confidence: 99%
“…One of the gaps in our knowledge, and the main objective of the featured study by Picetti et al [7], was to explore the role of ICP monitoring in traumatic brain injury (TBI) patients after primary decompressive craniectomy. BPrimary^in this context refers to DC during evacuation of an intracranial lesion in the acute phase.…”
mentioning
confidence: 99%
See 1 more Smart Citation